The enhanced delivery of salinomycin to CD133(+) ovarian cancer stem cells through CD133 antibody conjugation with poly(lactic-co-glycolic acid)-poly(ethylene glycol) nanoparticles - Mi, Yi (Oncol Lett, 2018)
Ovarian cancer is the most lethal gynecologic malignancy, and ovarian cancer stem cells (CSCs) serve a pivotal function in the metastasis and recurrence of ovarian cancer. Multiple previous studies have validated CD133 as a marker of ovarian CSCs. Although salinomycin is a promising therapeutic agent that has been demonstrated to kill CSCs in various types of cancer, poor aqueous solubility hampers its clinical application. The present study used salinomycin-loaded poly(lactic-co-glycolic acid)-poly(ethylene glycol) nanoparticles conjugated with CD133 antibodies (CD133-SAL-NP) to eliminate CD133(+) ovarian CSCs. The results revealed that CD133-SAL-NPs were of an appropriate size (149.2 nm) and exhibited sustained drug release. CD133-SAL-NPs efficiently bound to CD133(+) ovarian cancer cells, resulting in an increased cytotoxic effect in CD133(+) ovarian cancer cells, compared with the untargeted SAL-NPs and salinomycin. CD133-SAL-NPs reduced the percentage of CD133(+) ovarian CSCs in ovarian cells more effectively than treatment with salinomycin or SAL-NPs, suggesting that CD133-SAL-NP targeted CD133(+) ovarian CSCs. In nude mice bearing ovarian cancer xenografts, CD133-SAL-NPs exerted improved therapeutic effects compared with SAL-NPs and salinomycin. Thus, CD133 was demonstrated to be a promising target for drug delivery to ovarian CSCs, and may be useful as an agent to inhibit the growth of ovarian cancer by targeting CD133(+) ovarian CSCs. CD133-SAL-NPs may therefore represent a promising approach for the treatment of ovarian cancer.